ChemInform Abstract: Synthesis of Oxindoles by Broensted Acid Catalyzed Radical Cascade Addition of Ketones. Issue 2 (23rd December 2015) - Boess, Esther; Karanestora, Sofia; Bosnidou, Alexandra‐Eleni; Schweitzer‐Chaput, Bertrand; Hasenbeck, Max; Klussmann, Martin
Abstract: N‐alkylated methacrylic acid anilides react with ketones via tBuOOH‐mediated radical cascade Michael addition/cyclization to the title compounds in good to high yields.